What is the impact of mental health-related stigma on help-seeking? A systematic review of quantitative and qualitative studies. Issue 1 (21st February 2014) - Clement, S.; Schauman, O.; Graham, T.; Maggioni, F.; Evans-Lacko, S.; Bezborodovs, N.; Morgan, C.; Rüsch, N.; Brown, J. S. L.; Thornicroft, G.
Abstract : Background: Individuals often avoid or delay seeking professional help for mental health problems. Stigma may be a key deterrent to help-seeking but this has not been reviewed systematically. Our systematic review addressed the overarching question: What is the impact of mental health-related stigma on help-seeking for mental health problems? Subquestions were: ( a ) What is the size and direction of any association between stigma and help-seeking? ( b ) To what extent is stigma identified as a barrier to help-seeking? ( c ) What processes underlie the relationship between stigma and help-seeking? ( d ) Are there population groups for which stigma disproportionately deters help-seeking? Method: Five electronic databases were searched from 1980 to 2011 and references of reviews checked. A meta-synthesis of quantitative and qualitative studies, comprising three parallel narrative syntheses and subgroup analyses, was conducted. Results: The review identified 144 studies with 90 189 participants meeting inclusion criteria. The median association between stigma and help-seeking was d  = − 0.27, with internalized and treatment stigma being most often associated with reduced help-seeking. Stigma was the fourth highest ranked barrier to help-seeking, with disclosure concerns the most commonly reported stigma barrier. A detailed conceptual model was derived that describes the processes contributing to, and counteracting, the deterrent effect of stigma on help-seeking. Ethnic minorities, youth, men and those in military and health professions were disproportionately deterred by stigma. Conclusions: Stigma has a small- to moderate-sized negative effect on help-seeking. Review findings can be used to help inform the design of interventions to increase help-seeking.